2011
DOI: 10.1002/app.34427
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photochromic properties of naphthopyran polymer containing photocrosslinkable coumarin moiety

Abstract: Naphthopyran homopolymer and copolymer containing coumarin in side chain were synthesized by atom transfer radical polymerization. Their photochromic properties were investigated using UV-vis absorption spectroscopy and their decoloration kinetics in films was quantified by biexponential fitting of their photochromic decoloration curves after UV irradiation. The results showed that the photochromism and photocrosslinking occurred simultaneously under UV irradiation, and the photocrosslinking of coumarin reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…UV irradiation of these uncolored molecules leads to the formation of highly conjugated colored species that, in the absence of light, return thermally, with variable speed, to the closed form . The phenomen occurs in solution or when the molecules are dispersed in polymeric matrices, although the kinetics of the process is highly affected by the nature of the host matrix. The relative ease of chemical synthesis, the versatility of the photochromic activity, the thermal stability, and the notable fatigue resistance made these compounds the most commercially important class of photochromic molecules used for the production of photochromic plastic ophthalmic lenses that show a rapid and reversible color change at room temperature when exposed to the sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…UV irradiation of these uncolored molecules leads to the formation of highly conjugated colored species that, in the absence of light, return thermally, with variable speed, to the closed form . The phenomen occurs in solution or when the molecules are dispersed in polymeric matrices, although the kinetics of the process is highly affected by the nature of the host matrix. The relative ease of chemical synthesis, the versatility of the photochromic activity, the thermal stability, and the notable fatigue resistance made these compounds the most commercially important class of photochromic molecules used for the production of photochromic plastic ophthalmic lenses that show a rapid and reversible color change at room temperature when exposed to the sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wang et al demonstrated a reduced decoloration of a copolymer bearing naphthopyran and Cou7 moieties in the side-chains due to the preferred dimerization of the coumarin in comparison to the photoinduced ring-opening of the naphthopyran. 164 The copolymers were obtained by ATRP using CuBr complexed with PMDETA as catalyst and ethyl-bromoisobutylate as initiator. In contrast, a living cationic polymerization of Cou8 was reported by Minoda and coworkers.…”
Section: Coumarinsmentioning
confidence: 99%
“…Previous studies showed that the molecular structure and properties of the medium in which photochromic dyes are dispersed play a very important role with respect to the photochromic performance of these dyes . Properties of the medium such as chain stiffness, viscosity, polarity, and fractional free volume affect the photochromic activity by, for example, constraining the rotational mobility of the dyes.…”
Section: Introductionmentioning
confidence: 99%